Wakalah Financing Guarantee Law and Risk Management in Sharia Financial Institutions - Ilham Nardi Yulianto Ilham; Panji Marboro; Fauzul Masyhudi (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
This paper discusses the theory of guarantees on financing associated with wakalah contracts and also risk management in Islamic Financial Institutions (LKS). This research is a qualitative research using a normative juridical approach. Analysis and presentation of data will be using analytical descriptive method. The data collection method used in this paper is a library study or documentation study. The author is of the view that the shahibul maal financial institution in the form of shahibul maal gains the trust of everyone to carry out the mandate to use funds in a fair and correct manner and must be followed by the correct bonds and conditions in accordance with Islamic law, so as to be able to benefit all those concerned. Islamic banks as one of the sharia financing institutions must have guidelines for Islamic provisions, as well as for carrying out economic activities. Islamic banks must always pay attention to obtain profits, so that it is good if banks and customers are in accordance with Islamic law and regulations.